Melestarikan Budaya Anjat Dayak: Analisis Dampak Pelatihan Visual Communication Skill Terhadap Penguatan SDM Usaha Rumahan Jessie Samarinda - Nur Wahitdah; Iva Dwi Sari; Ella Anggriani; Relma Reifana Hero; Ismail Lukman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Globalization has brought significant changes to various aspects of life, including culture. Amid the influx of foreign cultures, local products such as the Anjat Dayak bag from the Dayak tribe face the threat of extinction. This research aims to preserve and promote the Anjat Dayak bag through training in visual communication skills to enhance the product's competitiveness and marketing. The study was conducted in Samarinda City, East Kalimantan, focusing on the Jessie Samarinda Home Business. This research employs a quantitative method (survey) and involves training the owner and employees of the home business in various aspects of visual communication skills. The training aims to improve digital marketing skills to boost sales and introduce the Anjat Dayak bag to the wider community. The research results show an 81.10% increase in the partners' knowledge and digital marketing skills. Thus, the competitiveness and sales of the Anjat Dayak bag are expected to increase, ensuring the preservation of Dayak culture.